Smartphone addiction and creativity in Chinese undergraduates: a moderated mediation model analysis - Cheng, Li; Xie, Han (Frontiers in Psychiatry, 2025)
ObjectivesIn the digital era, the relationship between smartphone addiction and creativity among Chinese undergraduates has drawn increasing attention. This study aimed to explore how depression mediates the relationship between smartphone addiction and creativity, and how positive rumination moderates this mediating effect, with the goal of clarifying the underlying psychological mechanisms and providing insights for promoting creativity and mental well - being among this population.​MethodsA cross - sectional study was carried out. Undergraduate students from three Chinese provinces were sampled through a questionnaire distributed via the Wenjuanxing online platform. The questionnaire measured smartphone addiction, depression, creativity, and positive rumination. A total of 401 valid responses were obtained. Moderated mediation analysis was employed to examine the relationships among these variables.​ResultsThe analysis showed that smartphone addiction significantly predicted depression, but had no significant direct effect on creativity. Depression negatively predicted creativity. It was confirmed that depression mediated the relationship between smartphone addiction and creativity. Moreover, positive rumination moderated the relationship between depression and creativity, and a protective effect was observed when the level of positive rumination was higher. The moderated mediation model proposed in this study was validated.ConclusionsThe study successfully validated the moderated mediation model, indicating that positive rumination weakens the negative impact of depression on creativity in the context of smartphone addiction. The findings suggest that positive rumination can potentially help alleviate the adverse effects of excessive smartphone use on the creative thinking of Chinese undergraduates.